1994
DOI: 10.1097/00000658-199411000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effect of Adjuvant Postoperative Chemoradiotherapy for Rectal Carcinoma on Bowel Function

Abstract: ObjectiveThe authors assessed the long-term effect of postoperative chemoradiotherapy on bowel function. Summary Background DataAdjuvant postoperative radiation therapy, often combined with chemotherapy, is being used increasingly often for rectal carcinoma. However, the long-term effect of this treatment on bowel function has not been investigated. MethodsThe records were reviewed of all patients undergoing anterior resection for rectal carcinoma 2 to 5 years previously. During this period, patients with Astl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
2
13

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(143 citation statements)
references
References 29 publications
6
122
2
13
Order By: Relevance
“…However, the frequency with which pelvic radiotherapy leads to side effects affecting QOL is not known. The literature suggests that it ranges from 6 to 78% of patients (Kollmorgen et al, 1994;Potosky et al, 2000;Gami et al, 2003;Kozelsky et al, 2003). This variation may reflect a true difference in chronic toxicity in different diseases using different techniques.…”
mentioning
confidence: 99%
“…However, the frequency with which pelvic radiotherapy leads to side effects affecting QOL is not known. The literature suggests that it ranges from 6 to 78% of patients (Kollmorgen et al, 1994;Potosky et al, 2000;Gami et al, 2003;Kozelsky et al, 2003). This variation may reflect a true difference in chronic toxicity in different diseases using different techniques.…”
mentioning
confidence: 99%
“…These include bowel obstruction, fistulation, intractable bleeding or secondary cancers. A further 6 -78% of patients develop less severe symptoms, which nevertheless detrimentally affect quality of life (Kollmorgen et al, 1994;Potosky et al, 2000;Gami et al, 2003). These may include urgency, frequency, faecal incontinence, diarrhoea, steatorrhoea, tenesmus, pain, constipation and weight loss .…”
mentioning
confidence: 99%
“…Letschert [36] in a retrospective review of 111 cases treated with radiation after rectal surgery, found a dose volume correlation for small bowel complications; the incidence of severe small bowel complications was 37% when 2 AP/PA large fields were used and 6% for limited threefield technique. The bowel function was assessed in detail by Kollmorgen et al [33] in a group of 100 cases with a minimum of 2 years follow-up after anterior resection of the rectum; 41 received postoperative chemoradiation, while 59 were only operated; night time bowel movements were present in 46% in the first group vs. 19% in the second, occasional incontinence in 39% vs. 17%, fecal urgency in 78% vs 19%. The LR rates reported after postoperative radiotherapy in the studies reviewed are between 6% and 25%.…”
Section: Andresultsmentioning
confidence: 99%